Schisandrae Fructus Reduces Symptoms of 4-Vinylcyclohexene Diepoxide-Induced Ovarian Failure in Mice - Dasom Shin (Evidence-Based Complementary and Alternative Medicine, 2017)
Menopause is associated with a decrease in the level of sex hormones such as ovarian estradiol and progesterone and can cause various symptoms such as depression, hot flash, fatigue, heart palpitations, and headache. Furthermore, there is a risk of developing complications such as osteoporosis, cardiovascular diseases, Alzheimer’s disease, and ovarian cancer. Schisandrae Fructus (SF) is widely used in Korean medicine as a cure for such complications. This study was conducted to evaluate the therapeutic effects of SF against menopause symptoms associated with follicle depletion caused by the industrial chemical 4-vinylcyclohexene diepoxide (VCD) in mice. VCD directly targets the preantral follicles. Mice were injected with VCD (160 mg/kg intraperitoneally) daily for 15 days and then with SF dosage 3 times/week for six weeks. To evaluate the effects of SF, body weight, tail skin temperature, uterine weight, lipid profile, and osteocalcin levels were measured. A decrease in body weight and tail skin temperature and an increase in uterine weight were observed upon SF treatment. Moreover, SF treatment significantly decreased total cholesterol, triglyceride, osteocalcin, and low-density lipoprotein levels and low-density/high-density lipoprotein ratio. These results suggest the potential use of SF in the treatment of menopausal symptoms in women.